2009
DOI: 10.1017/s0031182009006234
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Immunology of mosquito-malaria interactions: Of non-natural versus natural model systems and their inferences

Abstract: There has been a recent shift in the literature on mosquito/Plasmodium interactions with an increasingly large number of theoretical and experimental studies focusing on their population biology and evolutionary processes. Ecological immunology of mosquito-malaria interactions -the study of the mechanisms and function of mosquito immune responses to Plasmodium in their ecological and evolutionary context -is particularly important for our understanding of malaria transmission and how to control it. Indeed, des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 48 publications
2
30
0
Order By: Relevance
“…The likely dynamic nature of vector-parasite interactions could mean that much of the current research that does not take this into account may have been misinterpreted [25]. This study reiterates what has previously been suggested that researching vector-parasite interactions in unnatural couples, which could be due to using lab strains, artificial species combinations or simply geographically isolated vectors and parasites, molecular interactions uncovered could differ drastically to those found in nature [7], [63][64]. On top of that, on uncovering a molecular basis to, for example, mosquito resistance to malaria, the magnitude of its effect cannot be determined until it is tested in multiple sympatric couples.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The likely dynamic nature of vector-parasite interactions could mean that much of the current research that does not take this into account may have been misinterpreted [25]. This study reiterates what has previously been suggested that researching vector-parasite interactions in unnatural couples, which could be due to using lab strains, artificial species combinations or simply geographically isolated vectors and parasites, molecular interactions uncovered could differ drastically to those found in nature [7], [63][64]. On top of that, on uncovering a molecular basis to, for example, mosquito resistance to malaria, the magnitude of its effect cannot be determined until it is tested in multiple sympatric couples.…”
Section: Discussionsupporting
confidence: 52%
“…Selective pressures exerted by the parasite on its host and vice versa are expected to drive evolution for each to maximize its fitness. In the vectorial stages, evolutionary forces will favor the parasites with the highest transmission [7], this could lead to adaptation between sympatric parasite and vector populations due to local adaptation [8]. The factors that regulate the success and level of infection in the malaria vectors are now under scrutiny but the role of natural population diversity and geographical variations remain overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the isolation of individuals from the wild to controlled laboratory conditions for several generations alters the selective pressures imposed on them and may modify the expression of wild traits. In research conducted on vector- Plasmodium , studies may differ substantially in terms of these characteristics [62]. Here, we studied a natural ( Culex pipiens - Plasmodium relictum ) and wild (mosquitoes hatched from clutches collected on the field and Plasmodium strain was isolated since two years) vector-parasite association.…”
Section: Discussionmentioning
confidence: 99%
“…This may increase the chances of detecting an eventual pleiotropic effect of the insecticide resistance genes, but the results may not be necessarily applicable to other genetic backgrounds, particularly if there are epistatic interactions between the insecticide resistant genes and other genes in the genome (although modifier genes have not yet been described in this species [33]). The field-collected mosquitoes, on the other hand, allowed us to test the effects under the more realistic conditions of a heterogeneous genetic background [34]. Combined, these two approaches provide a powerful test of the role of insecticide resistance on parasite development within the mosquito.…”
Section: Introductionmentioning
confidence: 99%